Investigation of the Relationship between the Starting Age of Substance, Alcohol, Cigarette Use, Attachment Styles, and Temperament Features of Substance Users - Tuncay, Ahmet Fatih; Kıran, Binnaz; Çakmak, Soner (Addicta: The Turkish Journal on Addictions, 2021)
In this study, temperament characteristics, age at onset of substance use, alcohol and smoking, and attachment styles of individuals using drugs or stimulants subject to the obligation of probation were examined. The study was conducted with 328 volunteers in the probation directorate in 2019. Personal information form, attachment styles in interpersonal relations scale, and temperament and character inventory revised form have been applied to the participants. The Pearson product-moment correlation coefficient was used to determine whether the age at which the participants started using substances (drugs, cigarettes, and alcohol) was related to each other and to the sub-dimensions of the temperament inventory, and a t-test was used to examine the differences. In conclusion, it has been found that there is a significant relationship between the ages of onset of alcohol and cigarette use and the ages of substance use onset in this study. In addition, while it has been found that the attachment styles have not shown a significant difference according to the smoking variable, the anxious attachment of alcohol users have been found to be high, and the secure attachment of those treated in the Alcohol and Drug Addicts Treatment and Research Centre have been found to be significantly low.
Keywords: Age; alcohol; attachment styles; cigarette; probation; substance users; temperament features